A remarkably tunable emission from red to yellow to green in Mn4+-activated CaAl12O19 phosphor via co-doping Bi3 - Zhao, Caiyue; Xu, Yudong; Wang, Lei; Chen, Xinyi; Hu, Wenjie; Dai, Zhaoxiang; Hu, Mengyuan; Liu, Kai; Shi, Min (Journal of materials science. Materials in electronics, 2019)
In this study, Bi 3+ and Mn 4+ co-doped CaAl 12 O 19 phosphors were prepared via high-temperature solid-state reaction method, and their crystal structure, particle morphologies, luminescence properties, charge compensation mechanism and crystal field effect were investigated in detail. A most remarkable tuning effect can be achieved when the Bi 3+ concentration is 5% in CaAl 12 O 19 :Bi 3+ , 0.05% Mn 4+ and the electric multipolar interaction is inferred to be the main mechanism for concentration quenching effect. It is also found that, as charge compensators rather than sensitizers, Bi 3+ ions can effectively tailor the emissions in a wide range through partial reducing Mn 4+ to Mn 2+ . The charge compensation physics presumably involves the shift of Fermi energy level ( E F ) and variations of valence states of manganese ions after Bi 3+ introduction. Moreover, the authors calculated the splitting energy (Δ) and Racah parameters ( B and C ) for Mn 4+ in octahedral sites and Mn 2+ in tetrahedral sites by combining excitation spectra with Tanabe-Sugano diagram. The experimental results will be of certain helpfulness in developing phosphors used in white LED.